A Novel Intranasal Vaccine With PmpGs + MOMP Induces Robust Protections Both in Respiratory Tract and Genital System Post Chlamydia psittaci Infection - Li, Qiang; Chen, Siyu; Yan, Zhuanqiang; Fang, Huanxin; Wang, Zhanxin; He, Cheng (Frontiers in Veterinary Science, 2022)
Chlamydia psittaci (C. psittaci) is a crucial zoonotic pathogen that causes severe respiratory and reproductive system disease in humans and animals. In our pioneer study, polymorphic membrane protein G (PmpG) mediated attachment to host cells as the adhesions and induced immunity against C. psittaci infection. We hypothesize that multiple PmpG antigens adjuvanted with Vibrio cholerae ghost (VCG) and chitosan gel might trigger full protection via the intranasal route (i.n). In the present study, 40 SPF chickens were randomly divided into 4 groups, including the PmpG+MOMP, major outer membrane protein (MOMP), PmpGs (Pmp17G+Pmp20G+Pmp21G), and control groups (VCG+chitosan gel). Post twice immunizations, the PmpG+MOMP group yielded highly level-specific IgG, IgA antibodies and lymphocyte proliferation. As for cytokines, IFN-γ expression was upregulated significantly while IL-10 concentration was downregulated in the PmpG+MOMP group compared to other groups. In the second experiment, 100 breeder ducks were divided into the PmpG+MOMP group (i.n), the commercial MOMP group (via intramuscular injection, i.m), the inactivated EBs group (i.n), and the control group (i.n), 25 ducks per group. Post challenge, reduced egg production recovered soon in the inactivated EBs group and the PmpG+MOMP group. Moreover, the aforementioned two groups induced higher robust IgG antibodies, lymphocyte proliferation, and IFN-γ secretions than the commercial MOMP vaccine did. Postmortem, lower bacterial loads of spleens were determined in the PmpG+MOMP group and the inactivated EBs group. However, bacterial clearance of follicular membranes and shedding from the vaginal tract were not significant difference among three tested groups. Furthermore, the PmpG+MOMP group induced lower inflammations in the follicles and oviducts. Based on the above evidence, the combination of PmpG and MOMP adjuvanted with chitosan gel and VCG via intranasal route could induce full protection both in the respiratory system and genital tract post C. psittaci infection. More importantly, the combination antigen is superior to the inactivated EBs antigen due to no contamination to the environment and less genital inflammation. The combination of PmpG+MOMP adjuvanted with VCG and chitosan gel might be a promising novel vaccine by blocking C. psittaci infection from animals to human beings.